(untitled) (Revista Lusófona de Educação, 2026)
In a global context where conservatism has deepened social inequalities, schools continue to reproduce practices and discourses that marginalize dissident identities. This study analysed how teachers and students from a Portuguese school cluster perceive issues of gender and sexuality, seeking to understand whether normative views prevail or more inclusive perspectives emerge. The qualitative, descriptive, and exploratory research was conducted through two focus group sessions: one with students and another with teachers. Participants’ narratives, examined through content analysis (students) and critical discourse analysis (teachers), were organized into emerging categories and subsequently cross-referenced to identify convergences and divergences. The results reveal tensions between the recognition of diversity and the persistence of prejudice. Among students, a critical awareness was observed, though still constrained by normativities embedded in school relations. Among teachers, structural constraints were identified, reinforced by formative weaknesses and institutional pressures, although some fragmented initiatives of reflective practice were also noted. It is concluded that the school remains a symbolic arena where reproduction and transformation of gender and sexuality issues coexist, reinforcing the need to expand spaces for dialogue and shared responsibility.